2023
DOI: 10.1111/jocd.15486
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of consumer adoption of halal cosmetics: A systematic literature review

Abstract: Background:The global halal cosmetics market is projected to grow during the forecast period. However, the factors that influenced consumers in the world to opt for halal cosmetics remain ambiguous. Objectives:The objective of this study was to understand the universal concept of halal cosmetics and a framework of critical points that influence consumers in purchasing halal cosmetic products. Method:The method used was Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…Halal safety certificate refers to presence of the Halal emblem on products, which denotes a testing procedure based on the qualification of Halal products to ensure compliance with Halal Islamic consumers’ product requirements [ 62 ]. A few Southeast Asian studies indicated that Halal safety certificate and attitudes toward Halal products substantially affected the buying intention for cosmetic products [ 62 , 64 , 65 ]. However, Ahmad et al showed that knowledge of the products’ Halal logo does not significantly affect consumer intention in purchasing cosmetic products [ 62 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Halal safety certificate refers to presence of the Halal emblem on products, which denotes a testing procedure based on the qualification of Halal products to ensure compliance with Halal Islamic consumers’ product requirements [ 62 ]. A few Southeast Asian studies indicated that Halal safety certificate and attitudes toward Halal products substantially affected the buying intention for cosmetic products [ 62 , 64 , 65 ]. However, Ahmad et al showed that knowledge of the products’ Halal logo does not significantly affect consumer intention in purchasing cosmetic products [ 62 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mohd Subri et al (2022) applied the SLR analysis to the area of halal cosmetics by focusing on the research trends and opportunities of halal cosmetics. Meanwhile, Isa et al (2023) conducted an SLR on the research related to consumer adoption of halal cosmetics. Therefore, the SLR analysis in this research area is necessary.…”
Section: Systematic Literature Review On Halal Cosmetics Supply Chainmentioning
confidence: 99%
“…According to Isa et al (2023), the industry of halal cosmetics is a rapidly growing segment of the global cosmetics industry, driven by the increasing demand from Muslim consumers who want to use products that align with their religious beliefs and values. Halal cosmetics are popular not only amongst Muslim consumers but also among non-Muslims who want natural and organic products.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of close peers contributes to Muslim preferences toward halallabeled products (Kasri et al, 2023). Despite having preferences toward a particular brand, they tend to consider their peer's recommendations to choose a genuinely halal brand, represented by a halal logo (Isa et al, 2022). Also, opinions from others considered as close friends or essential people encourage them to seek the halal label before purchasing (Suleman et al, 2021):…”
Section: Theory Of Planned Behavior and Halal Label Perceived Importancementioning
confidence: 99%
“…HPI mediates the relationship between PBC and BI. Wilson and Grant (2013) Social pressure motivates individuals to act according to their religious peer group to search for the halal label before making any purchase decision Isa et al (2022) Muslims tend to consider their peer's recommendations to choose genuinely halal brand, represented by a halal logo Suleman et al (2021) Opinions from others considered as close friends or important people encourages Muslims to seek the halal label before making a purchase H6 : PBC positively influences HPI Saville and Mahbubi (2021) Widely available halal products, mainly due to certification policy, enable Muslim consumers to seek the halal-labeled products Ahmadova and Aliyev (2021) The greater PBC over genuinely halal products make Muslims seek the halal logo availability H7 : HPI has a positive and significant influence on BI Rizkitysha and Hananto (2022) Muslims consider that it is mandatory for a product to have an official halal logo prior making purchase Elseidi (2018) Muslims perceive that halal logo is a trusted cue and strengthens the BI (continued)…”
Section: Small Medium Enterprises Segmentmentioning
confidence: 99%